Avaliação da cognição e da integridade axonal do nervo óptico em pacientes com síndrome clinicamente isolada - Carolina Fiorin Anhoque (2012)
Background: Several studies showed cognitive impairment in multiple sclerosis (MS), however, few studies evaluated cognition in patients with clinically isolated syndrome (CIS). Also, little is known about neuropsychiatric aspects and quality of life among CIS patients. Objectives: The aims of this study were to investigate cognitive impairment, psychiatric abnormalities, quality of life, and optical nerve damage in patients with CIS, and to assess the correlations betweenthese variables. Methods: This cross-sectional study was conducted on a sample of 18 patients with CIS and a control group (n = 18) with healthy subjects matched by gender, age, education level, and hand-dominance. Patients and controls were submitted to a battery of tests for cognitive assessment, inventories of depression and anxiety; neurological disability assessment (GNDS), evaluation of quality of life (DEFU), and optical coherence tomography (OCT) in both eyes. Expanded scale of disability status (EDSS), Adult Intelligence Scale - WAIS III (short form- the subtests vocabulary and picture) and mini-exam of mental status were used. Continuous data were compared using the Mann-Whitney test and proportions were compared with contingency tables using the chi-square or Fischers test. The correlations between the thickness of the optic nerve, cognitive data, anxiety and depression sores were assessed with the Spearman test. The significance level was set at p <0.05. Results: CIS patients had significant worse performance in Paced Auditory Serial Addition Test (PASAT) 2 seconds (P=0.009) and verbal fluency tests (P=0.0038) than controls. There was a significant differencein quality of life (QoL) between CIS patients and controls (P=0.000). There was a significant difference in BAI (P=0.003), but not significant difference in BDI between patients and controls was found. There were significant correlations between QoL measure and verbal fluency and Stroop test but not with neurological disability, depression, and anxiety. Optical nerve axonal loss was found more frequently in eyes with previous optic neuritis (ON) (85.7%) than in those without previous ON (21.7%) (P=0.0146). There were no significant correlations between opticalnerve axonal loss and cognitive findings. Conclusion: CIS patients had worse cognitiveperformance than controls in executive functions tests. Cognition, but not anxiety, depression and disability, was associated with reduced quality of life. OCT evaluation showed to be able to detect axonal loss resulting from optical neuritis as well as subclinical axonal loss in eyes without previous optical neuritis; however, optical nerve axonal loss was not correlated with cognition.